Reconfiguration of DNA nanostructures induced by enzymatic ligation treatment. Issue 14 (26th July 2022) - Bai, Tanxi; Zhang, Jiayi; Huang, Kai; Wang, Wen; Chen, Bowen; Li, Yujie; Zhao, Mengyao; Zhang, Suoyu; Zhu, Chenyou; Liu, Dongsheng; Wei, Bryan
Abstract: Enzymatic ligation is a popular method in DNA nanotechnology for structural enforcement. When employed as stability switch for chosen components, ligation can be applied to induce DNA nanostructure reconfiguration. In this study, we investigate the reinforcement effect of ligation on addressable DNA nanostructures assembled entirely from short synthetic strands as the basis of structural reconfiguration. A careful calibration of ligation efficiency is performed on structures with programmable nicks. Systematic investigation using comparative agarose gel electrophoresis enables quantitative assessment of enhanced survivability with ligation treatment on a number of unique structures. The solid ligation performance sets up the foundation for the ligation-based structural reconfiguration. With the capability of switching base pairing status between permanent and transient (ON and OFF) by a simple round of enzymatic treatment, ligation induced reconfiguration can be engineered for DNA nanostructures accordingly.